The Sociology of Sport in Germany: Development and Recent Trends - Jan Haut; Michael Staack; Lukas Schwank (Universidad Pablo de Olavide, 2020)
As a reply to a contribution informing about the situation in Spanish sociology of sport (Sánchez-García, Moscoso-Sánchez and Piedra 2020), we give an overview on the development and recent trends of the sociology of sport in Germany. We start with a historical account of its institutionalization, and then follow up with an overview of established research topics and theoretical perspectives. For that, we draw on established German textbooks and introductions to the sociology of sport. Afterwards, regarding more recent trends, we focus on the development of the journal "Sport und Gesellschaft - Sport and Society". Finally, we describe how the sociology of sport within German sociology relates to the sociology of sport within sport sciences. We conclude our contribution by comparing developments in Spain and Germany, in order to identify similar international challenges for the sociology of sports and its journals.